(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Radiology is essential to modern healthcare, but advanced imaging modalities such as magnetic resonance imaging and computed tomography are highly energy-intensive. Continuous equipment operation, cooling systems, and digital infrastructure significantly increase electricity use and carbon emissions. With growing climate concerns and healthcare energy demands, integrating sustainability into radiology practice is crucial within the One Health framework. Aim & Objectives: This study aimed to evaluate the electricity consumption profile of a hospital radiology department and assess the impact of structured energy-efficiency interventions. The objectives were to identify major energy-consuming equipment, quantify baseline electricity use, and determine potential reductions achievable through uniform efficiency measures. Materials & Methods: This observational, evidence-based assessment evaluated the monthly electricity consumption of radiology and HVAC equipment before and after a standardized 30 percent energy-efficiency intervention. Equipment-wise power use was recorded, categorized, and compared to determine absolute and relative reductions in energy demand. Results: Baseline analysis demonstrated a highly skewed consumption pattern, with the MRI system accounting for more than half of total monthly electricity use, followed by air conditioning and CT scanners. After intervention, total monthly consumption decreased from 24,419 kWh to 17,094 kWh, achieving a net reduction of 7,325 kWh. The largest absolute savings were observed in MRI, HVAC systems, and CT scanners, while low-power devices showed minimal impact. Conclusion: Targeted energy optimization in high-load imaging and climate control systems can produce substantial electricity savings without compromising diagnostic services. Adoption of sustainable radiology practices represents a practical pathway to reduce healthcare carbon footprint while supporting environmental and public health goals.